Predictors and consequences of diet composition in a declining generalist aerial insectivore - Jennifer J. Uehling; Conor C. Taff; Jennifer L. Houtz; Paige M. Becker; Allison S. Injaian; Maren N. Vitousek (Oecologia, 2026)
For generalist animals that have a broad range of food choices, the specific diet characteristics that are important for health and fitness are often unclear. Here, we examine whether individual variation in diet composition predicts nestling mass and fledge success, and we identify potential drivers of variation in diet composition, in a declining generalist aerial insectivore, the tree swallow ( Tachycineta bicolor ). We collected morphological measurements, feces, and fledge success information from adult and nestling swallows. We then used DNA metabarcoding of 429 fecal samples to characterize swallow diets. We focused on two diet characteristics that may be important for generalists: dietary diversity and prevalence of nutritionally important diet items, specifically aquatic insects, which are essential to tree swallows. We predicted that nestlings with more diverse diets that were composed of a higher proportion of aquatic arthropods would be more likely to survive to fledging, and that adults’ phenotypes and their stage in the breeding season would be associated with both their own diets and the diets of their nestlings. Swallow nestling dietary diversity strongly predicted fledge success, but we found no link between dietary aquatic arthropod content and nestling fledging. Adult phenotype did not predict nestling diet, but during the provisioning period, adult females with lower body mass had more diverse diets. Because this study occurred during a single breeding season in one geographic area, future work should further explore the patterns observed here, and especially examine the importance of dietary diversity for wild generalist species across years and localities.